2013
DOI: 10.1123/ijspp.8.4.442
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time of Day on Cold Water Ingestion by High-Level Swimmers in a Tropical Climate

Abstract: The authors tested the effect of cold water ingestion during high-intensity training in the morning vs the evening on both core temperature (TC) and thermal perceptions of internationally ranked long-distance swimmers during a training period in a tropical climate. Nine internationally ranked long-distance swimmers (5 men and 4 women) performed 4 randomized training sessions (2 in the evening and 2 in the morning) with 2 randomized beverages with different temperatures for 3 consecutive days. After a standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 25 publications
5
37
0
Order By: Relevance
“…In addition, a lower RPE in the run segment of the triathlon might be particularly advantageous, making the combined strategy more effective than the internal midcooling strategy alone. The attenuated rise in T co observed in swimmers when they absorb cold water could be considered as internal precooling for the subsequent cycle segment, and would thereby lead to reduced RPE at the end of cycling [15]. Consequently, triathletes would start running with a lower RPE.…”
Section: Perspectivesmentioning
confidence: 99%
“…In addition, a lower RPE in the run segment of the triathlon might be particularly advantageous, making the combined strategy more effective than the internal midcooling strategy alone. The attenuated rise in T co observed in swimmers when they absorb cold water could be considered as internal precooling for the subsequent cycle segment, and would thereby lead to reduced RPE at the end of cycling [15]. Consequently, triathletes would start running with a lower RPE.…”
Section: Perspectivesmentioning
confidence: 99%
“…Commonly used cryotherapy procedures consist of external applications, such as cold packs,5 ice cuffs,6 cold air,7 ice sprays,8 cold-water immersion (CWI),9 whole-body cryotherapy chambers,10 whole-body cryochambers using liquid nitrogen,11 cooling vests,12 or any other combination of these methods, as well as cold-water ingestion 13,14. The latter procedure has resulted in conflicting results 15,16…”
Section: Introductionmentioning
confidence: 99%
“…The ingestion of substantial volumes (6.5-7.5 g/kg BM) of ice slurries in the 30 min before exercise has been shown to improve endurance capacity and performance during terrestrial exercise (Ihsan et al, 2010;Siegel et al, 2010Siegel et al, , 2011Burdon et al, 2013). An investigation undertaken in a group of elite open-water swimmers demonstrated that ingestion of cold water significantly reduced core temperature and thermal sensation, particularly during an evening training session, in a warm pool (29 °C; Hue et al, 2013). The physiological mechanisms of such strategies are explained elsewhere .…”
Section: Precooling With Cold Beverages and Ice Slurriesmentioning
confidence: 99%